Knowledge about emergency management of dental trauma among school teachers of Bhaktapur Nepal - Pradhan, Megha; Joshi, Ujjwal; Aryal, Umesh Raj; Upadhyay, Sumita; Shrestha, Amrita (Journal of Kathmandu Medical College, 2017)
Background: Injury to a young child’s teeth and face is a traumatic experience for the child and parents. Prompt and effective action on traumatized teeth significantly increases the likelihood of a positive treatment outcome. Adequate knowledge of school teachers in emergency situation arising during school hours can prove to be a boon for the child’s oral health. Objectives: To assess the knowledge of school teachers of Bhaktapur about emergency management of dental trauma and also to measure the relationship between socio demographic characteristic of teachers and knowledge about dental emergencies. Methods: The cross sectional study was conducted among 424 schools teachers of Bhaktapur district from September 2014 to March 2015. Simple random sampling was done to select the schools. Questionnaire was distributed among the teachers after taking their informed written consent. Data was collected and sent for statistical evaluation. Frequencies and percentage were calculated. Chi-square and Fisher’s Exact test were applied. Results: Nearly one third (32.2%) teachers who had information on dental trauma knew the proper management of displaced teeth (p=0.01). Statistically significant difference was found among those who had fi rst aid training and proper management of displaced teeth (p=0.04). Teachers who had experienced dental trauma in their students were only confident of managing displacement of traumatized teeth (p=0.02). Conclusion: Knowledge of the school teachers in Bhaktapur was seen to be inadequate for emergency management of fracture and avulsed tooth.